2019
DOI: 10.1186/s40663-019-0181-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of persistent drought and waterlogging on the dynamics of nonstructural carbohydrates of Robinia pseudoacacia L. seedlings in Northwest China

Abstract: Background: The nonstructural carbohydrates (NSCs) of plants are posited to be crucial traits for the resistance and resilience of plants to climate change-induced drought and flooding. However, the potential effects of persistent drought and waterlogging on the dynamics of the NSCs and the underlying mechanisms are still poorly understood. Methods: We measured the NSCs concentrations and pool size, photosynthetic rate and biomass of Robinia pseudoacacia L. seedlings for both 2015 and 2016 under five soil wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 93 publications
4
11
0
1
Order By: Relevance
“…The adaptation mechanism of plants to the specific living environment is first manifested in morphology. Many studies have shown that drought stress significantly inhibits plant growth, such as the decline of plant height and biomass ( Zhang et al., 2018; Yang et al., 2019; Deng et al., 2020). Our study also reached a similar conclusion; specifically, under drought stress, the plant height, stem diameter, total biomass and biomass accumulation of roots, stems and leaves of R. pseudoacacia seedlings decreased, indicating the response of plants to drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…The adaptation mechanism of plants to the specific living environment is first manifested in morphology. Many studies have shown that drought stress significantly inhibits plant growth, such as the decline of plant height and biomass ( Zhang et al., 2018; Yang et al., 2019; Deng et al., 2020). Our study also reached a similar conclusion; specifically, under drought stress, the plant height, stem diameter, total biomass and biomass accumulation of roots, stems and leaves of R. pseudoacacia seedlings decreased, indicating the response of plants to drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…Robinia pseudoacacia (Black locust) is a leguminous tree which can rapidly fix nitrogen (N) from the atmosphere via Rhizobium (Zhang et al 2019) and further alter soil properties by increasing mineral N (Medina-Villar et al 2016). R. pseudoacacia is able to disperse quickly and colonize a broad range of xeric habitats, including steep rocks or toxic man-made substrata (Cierjacks et al 2013), and has been extensively naturalized in the temperate regions of North America, Europe, and Asia (Sabo 2000;Lee et al 2004;Vítková et al 2017;Yang et al 2019). Natural reproduction of R. pseudoacacia plantations is primarily vegetative through root suckering and stump sprouting, allowing vigorous regeneration after coppicing and disturbance (Peng et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Black locust (Robinia pseudoacacia) is a leguminous tree which can rapidly x nitrogen (N) from the atmosphere via Rhizobium (Zhang et al 2019) and further alter soil properties by increasing mineral N (Medina-Villar et al 2016). R. pseudoacacia is able to disperse quickly and colonize a broad range of xeric habitats, including steep rocks or toxic man-made substrata (Cierjacks et al 2013), and has been extensively naturalized in the temperate regions of North America, Europe, and Asia (Sabo, 2000;Lee et al 2004;Vítková et al 2017;Yang et al 2019). Natural reproduction of R. pseudoacacia plantations is primarily vegetative through root suckering and stump sprouting, allowing vigorous regeneration after coppicing and disturbance (Peng et al 2003).…”
Section: Introductionmentioning
confidence: 99%